Complementary Terminal Sliding Mode Control for Variable Speed Wind Turbine - Diaz-Diaz, M; Rajendran, S (Institute of Electrical and Electronics Engineers Inc., 2023)
The reduction in transient loads on the drive train influences the life span of the wind turbine when designing the controller for power extraction. In wind turbines, compromises between the efficiency of power extraction and the load level on the drive train have become key issues. Conventional control techniques enhanced energy extraction at the cost of a higher transient load on the drive train. Therefore, this work proposes the complementary terminal sliding mode controller for energy extraction whilst reducing the drive train load. A 600 kW FAST simulator is utilised to validate the performance of the proposed and conventional controllers. Finally, a detailed investigation has been conducted based on energy extraction and mitigation of transient loads under various turbulence models and mean wind speeds. © 2023 IEEE.